Ageless Assets: Social Investment and Active Aging Profiles in Lithuania - Vilkoitytė, Violeta (Socialinė teorija, empirija, politika ir praktika, 2024)
This article argues that the aging population significantly affects the welfare state. Social investment strategies could respond to a changed economic and social order by enhancing active aging. While the social investment perspective has been a topic of discussion for decades, certain aspects remain underexplored. This study, therefore, aims to assess the impact of social investments on active aging. The study, based on the social investment approach and active aging model, analyzes quantitative data from Wave 8 of the Survey of Health, Ageing and Retirement in Europe (SHARE). The Lithuania sample included 1437 participants. In the analytical phase, Principal Component Analysis and Cluster Analysis were utilized (SPSS ver. 26). The findings unveil four active aging profiles (low activity, moderate activity, balanced activity, and high activity). The two groups are distinguished by aging conditions, such as poor health, lack of social investment, and high reliance on social benefits. The positive impact of social investment is underscored by the improved aging conditions outlined in the last two profiles. This study enriches the social investment research domain by providing valuable insights into the influence of social investment policies on the lives of older individuals and their potential to age actively.